Big Data Analysis with MongoDB for Decision Support System - Sulistyo Heripracoyo; Roni Kurniawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
The big data is currently a growing topic in the world of information technology. Based on the literature mentioned that manage of big data can create significant value for the world economy, improving productivity and competitiveness of enterprises and the public sector as well as creating a large economic surplus for consumers. However, based on the information obtained, the big data is still not widely applied in the company or organization. This study aimed to explore more information about the big data and proceed with making an application prototype big data management. This experiment established with the big data storage that is database, this research use NoSQL database technology that can map the needs of both structured and unstructured. And this research will be carried out migration of Relational Database (RDBMS) into the database MongoDB.   Prototype will be create with the object of study is structured and unstructured data. The expected result of this research is a model or prototype of big data management that can help organizations and companies (especially education) to make decisions based on various types of data.